Angels and crowds - Varma, J. R. (SAGE Knowledge. Cases., 2015)
In mid 2014, two promising entrepreneurs, Kallidil Kalidasan and Nibu Alias, who needed to raise capital urgently, sought advice from Sanjay Vijaykumar, Chairman of Startup Village, on possible funding avenues and strategies. Startup Village was a technology business incubator in the state of Kerala in Southern India where both the entrepreneurs were being incubated.